The correlation between oral health knowledge & attitude towards practice of caretakers in day-care centres. - Ab. Halim, Noorhazayti; Yusof, Raihan Mastura; Abdullah, Siti Norazizah (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Modernization has made young children to spend most of their time in day-care centres as their mothers are working outside the home. Hence, the role of caretaker has become more important in the daily diet and oral health care of children. The objective of this study is to assess the oral health knowledge, attitude and practice among caretakers in day-care centres. A cross-sectional study among 54 caretakers aged 18 and above was conducted in Kuantan. The data was collected using a self-administered questionnaire addressing aspects of oral health knowledge, attitude and practice of caretakers. The results were analyzed by descriptive and Spearman correlation coefficient tests. The participants were mainly Malay ladies and 16.7% had university education. The knowledge of sugary food causing dental caries was found good for all caretakers; however, 48.1% of them do not know the important about filling the teeth of their children. Preliminary analysis was performed and followed by Spearman correlation coefficient analysis. Correlation between attitude and practice was weak (rho=0.29, p<0.05), and between knowledge and practice (rho=0.21, p>0.05). The caretakers had good oral health knowledge but it did not reflect in their attitude and practices. The action must be based on knowledge, and that knowledge must produce action. As Abu Bakr (R.A) said, “without knowledge action is useless and knowledge without action is futile.” The Arabic term ‘ilm translates to knowledge, but the word has a broader definition than its English counterpart. ‘Ilm encompasses theory, action, and education whereas in English, knowledge is defined as merely the awareness of facts, truths, and principles.